ANALISIS DISPARITAS PENDAPATAN PENGUSAHA TEMPE YANG BERADA DI DESA BENDUL MERISI KECAMATAN WONOCOLO SURABAYA - Indrianty, Exsanti Frida; Gunawan, Kunto Inggit (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2020)
This study aims to determine the income disparity of tempe entrepreneurs in Bendul Merisi Village, Wonocolo District, Surabaya. This research method uses descriptive quantitative methods using primary data, the data used are questionnaires obtained from tempe entrepreneurs respondents. The data analysis tool in this study is the Gini ratio. The results of this study can be explained that the total % of income in the first class is 0.11%, the second class is 0.15%, the third class is 0.18%, the fourth class is 0.23% and the fifth class is 0.33% with the total percentage of income by 100%. And it can be explained that there is a cumulative income in the first class of 0.11%, the second class of 0.26%, the third class of 0.44%, the fourth class of 0.67%, and the fifth class of 100%. Then, the Gini coefficient value (Gini Ratio) using the five-class method is 0.22, it can be seen that the level of income inequality of Tempe entrepreneurs in Bendul Merisi Village, Wonocolo District is in the category of low-income inequality.